Ancillary orders on Muslim divorce the practice of Syariah court in State of Johor / Wan Kuraishah Wan Talib - Wan Talib, Wan Kuraishah (Faculty of Law, 1986)
The increasing number of divorces in the State of Johor has caused great concern in our society. Statistics compiled by various syariah courts in Johor have revealed that the rate of divorce, even though fluctuating for the past five years, would tend to rise rapidly if no proper measures are taken to help to reduce it. In this way, the syariah courts and other religious departments play a vital role in helping to enforce the law on marriage and divorce, effectively having regards to the Quranic principles and the Sunnahs. The main purpose of this paper is to discuss the powers of the syariah court to make ancillary orders on divorce; emphasising on the role of Syariah Court as an Islamic judicial institution in the State of Johor to which the Johor Administration of Islamic Law Enactment, 1978 applies. The Muslim Law as administered in the State of Johor, like all other states, is varied by Malay Custom and applies to all Muslims but is subject in its application to variations in accordance with the school of law to which the partied belong. In Johor, the most prevalent school of thought followed by the Muslim here.is the Shafie School.